Impact of timing of the anorexigen sibutramine administration on reproductive end-points of male rats - Borges, Cibele S. [UNESP]; Silva, Patrícia V. [UNESP]; Lozano, Ana Flávia Q. [UNESP]; Missassi, Gabriela [UNESP]; Silva, Raquel F. [UNESP]; Anselmo-Franci, Janete A.; Kempinas, Wilma G. [UNESP] (Wiley, 2020)
Sibutramine is a non-selective serotonin-norepinephrine reuptake inhibitor orally administered for weight loss. In a previous study, we showed pharmacological mechanisms involved in the reduction of sperm quality and fertility of rats exposed for 30 days to this anorexigen in the light phase of the light-dark (l/d) cycle. It is already known that rodents are nightlife animals, with higher metabolic activity during the dark phase than in the light phase of the light-dark (l/d) cycle. Thus, the present study aimed to investigate whether the deleterious effects on reproductive parameters after sibutramine administration would be enhanced after a shorter period of exposure during the dark phase of the l/d cycle. For this, adult male Wistar rats were treated with sibutramine (10 mg/kg/d) or vehicle for 15 days during the dark phase of the l/d cycle. Sibutramine treatment decreased final body and reproductive organ weights, as well as serum testosterone levels. Sperm transit time through the epididymis was accelerated, and sperm concentration and motility were diminished in the sibutramine-exposed rats. The decrease in sperm concentration was also verified in the epididymal histological sections. In conclusion, the deleterious effects of sibutramine on reproductive parameters of male rats were enhanced when the exposure occurred in the dark phase of the l/d cycle, even after a short exposure duration. Our results reinforce the impact of timing on drug therapeutic action.
Keywords: chronopharmacology; drug toxicity; male reproductive tract; rat; sibutramine